Relation Between Ghrelin Hormone Levels and Bone Mineral Density in Normal Adults - Y Naghiaee; J Mohiti Ardakani; H Mozaffari-Khosravi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2011)
Introduction: Ghrelin hormone is a polypeptide with 28 amino acids that is secreted along the gastrointestinal tract, mainly in fundus of stomach. Some physiological functions of ghrelin include increase of appetite and food intake, energy balance, stimulation of growth hormone secretion and heart output and decrease in blood pressure. Recently, relation of ghrelin and bone mineral density has been considered. Methods: This descriptive study included 33 adult persons above 20 years of age. Bone mineral density was determined with dual energy x-ray absorptiometry in femur and lumbar regions. T-score over than -1 was considered as normal case. Ghrelin levels were determined by ELISA method. Results: The mean of age, body mass index and serum ghrelin were 40±10.6years, 27±3.6 kg/m² and 100.5±128 pg/ml, respectively. Correlation of ghrelin and variables was not statistically significant except weight (p=0.05). Conclusion: Range of serum ghrelin levels varies with age. In the present research, there was no relationship between ghrelin levels and bone mineral density in femur and lumbar regions. More studies with larger number of samples are proposed.